The relationship between children’s narrative retelling and other aspects of language skills - Ding, Y (2021)
Background & Aim: Oral language skills are a critical foundation for educational success. Oral language skills are typically assessed with standardised tests involving diverse measures with highly constrained responses (e.g. CELF receptive vocabulary and sentence repetition subsets). Another measure of language skill that is typically absent from standardised tests is narrative retelling, where a child hears a story and is required to retell it. The aim of the current study is to investigate the correlation between children’s narrative retelling and other aspects of oral language skills.